It is given that
![g(x)=x^3+3x^2-18x-40](https://img.qammunity.org/2023/formulas/mathematics/high-school/au4np5eijvdetbw6v1mqezziltmkdibntw.png)
The one factor of g(x) is (x+5).
By using the synthetic method, we get
![g(x)=(x+5)(x^2-2x-8)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4mxwrgha84feccn5g0sy2d06t8w5c55mdj.png)
![g(x)=(x+5)(x^2-4x+2x-8)](https://img.qammunity.org/2023/formulas/mathematics/high-school/miss4uzc1wzaw8jzrqvixt075edhetpwzy.png)
![g(x)=(x+5)(x(x-4)+2(x-4))](https://img.qammunity.org/2023/formulas/mathematics/high-school/7o7yijdbajb42588zph2wddlbmcu556lr4.png)
![g(x)=(x+5)(x-4)(x+2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/c5amw24xwcbv4psks5a8lrituuuqf64r32.png)
Hecne zeros of g(x) is -5,4, and -2.
2)
It is given that
![g(x)=x^3+x^2-17x+15](https://img.qammunity.org/2023/formulas/mathematics/high-school/iymesk23zhixqeflrlcwsh6ia77tv5ni6j.png)
The one zero of the given g(x) is x=1.
By using the synthetic method, we get
![g(x)=(x-1)(x^2+2x-15)](https://img.qammunity.org/2023/formulas/mathematics/high-school/2k5sd2r8ly4du2czpvffx731t5lg7gssem.png)
![g(x)=(x-1)(x^2+3x-5x-15)](https://img.qammunity.org/2023/formulas/mathematics/high-school/e9xoobka9cdardci7n2u2rv1urlzpobibs.png)
![g(x)=(x-1)(x(x+3)-5(x+3))](https://img.qammunity.org/2023/formulas/mathematics/high-school/22v4qtey37d7ie7dq59xxr4tpbzp54zmeu.png)
![g(x)=(x-1)(x+3)(x-5)](https://img.qammunity.org/2023/formulas/mathematics/high-school/rthsrmvtdf3647mbw5m5s73tbup636zfyv.png)
To find zeros of g(x) by equating g(x) to zero.
![g(x)=(x-1)(x+3)(x-5)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/9uijkdkmf7zwmbfvq7a6515mh0l34r7ik3.png)
![(x-1)=0;(x+3)=0;(x-5)=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/qmp7gsktfjxois3fxt5kk4i13beih53ujl.png)
![x=1;x=-3;\text{ x=5}](https://img.qammunity.org/2023/formulas/mathematics/high-school/qpbh2adh5mzgks2z79gsesi6vv13f3xxyj.png)
Hence the zeros of the given function g(x) are 1,-3, and 5.